(untitled) (Research, Society and Development, 2021)
This article proposes a theoretical model of the role of the human resources area in the internal organizational communication process with a focus on strategic alignment. The methodology used in the development of the research involved exploratory and descriptive aspects, through the use of literature review in the Scientific Electronic Library Online (SciELO) and Scopus platform. As a result of this research, a cyclic management model was structured, consisting of six steps. In each of them, a conceptual synthesis about the role of HR in the internal communication process was presented. In addition to the suggested conceptual synthesis, this article establishes a theoretical guide that can be useful for future research related to the topic.